Znaczenie turystyki dla rozwoju regionu małopolskiego - Bonarska-Treit, Alicja (The Importance of Tourism in Expansion of Małopolska's Region, 2009)
The subject of this article is the importance of tourism in expansion of Malopolska's region. At the beginning, it contains characteristics of region and its division. Next, it is shown the impact of tourism on social and economic development of region. The last part of article shows tourism as one of the most important branches of economy, which has a fundamental influence on expansion of Malopolska's region. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 507-513